1981
DOI: 10.1103/physrevd.24.1991
|View full text |Cite
|
Sign up to set email alerts
|

Bounds one+el*l

Abstract: The small limits of discrepancy between experimental and theoretical values of (g -Z),,, are shown to eliminate any chance of seeing single excited e*'s or p*'s in colliding-beam or inelastic electro-or muoproduction experiments. On the other hand, visible I* tracks in very-high-energy (E > lox9 eV) cosmic-ray events are possible for m;-1 TeV. The results presuppose a new dynamics, disjoint from QED, underlying the 1 * excitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The S2 flow was first identified in high resolution K I and Na I absorption spectra by Goldberg et al (1975) and subsequently re-observed multiple times over the next couple of years (Goldberg 1979). It is interesting to compare these and Bernat et al's (1979) CO line-ofsight absorption velocities with those from the CARMA emission spectra obtained at similar spectral resolutions and also to measure, the perhaps co-spatial line broadening of the K I S2 absorption feature.…”
Section: K I 7699å Spectramentioning
confidence: 79%
See 1 more Smart Citation
“…The S2 flow was first identified in high resolution K I and Na I absorption spectra by Goldberg et al (1975) and subsequently re-observed multiple times over the next couple of years (Goldberg 1979). It is interesting to compare these and Bernat et al's (1979) CO line-ofsight absorption velocities with those from the CARMA emission spectra obtained at similar spectral resolutions and also to measure, the perhaps co-spatial line broadening of the K I S2 absorption feature.…”
Section: K I 7699å Spectramentioning
confidence: 79%
“…high spectral resolution atomic Na and K absorption profiles (Goldberg et al 1975). 12 C 16 O was subsequently detected at 230 GHz in the J = 2 − 1 rotational emission line by Knapp et al (1980), although a search for SiO(J = 2 − 1) by Lambert & Vanden Bout (1978) had been unsuccessful.…”
Section: Introductionmentioning
confidence: 99%
“…The renal vasodilation and increase in renal blood flow produced by dopexamine HCI were blocked by SCH 23390, a potent and highly selective DA1receptor antagonist (Goldberg et a1 1984;Hilditch et all984) and this agrees with our earlier finding using bulbocapnine as a DAl-receptor blocker (Brown et al 1985b). The vascular DAl-receptor has a highly regional disposition and is particularly abundant in the renal vasculature (Goldberg 1972).…”
Section: Discussionmentioning
confidence: 99%
“…A t the present time, however, the existence of dopamine-containing peripheral autonomic neurons is uncertain. O n the other hand there exist differences between noradrenaline and dopamine which support the view that dopamine might in fact have some function at the periphery other than being solely a precursor substance for the biosynthesis of noradrenaline (for reviews see: HORNYKIEWICZ, 1971 ;GOLDBERG, 1972). We therefore studied the effect of dopamine on ruminal smooth muscle preparations in vitro and additionally investigated the influence of dopamine infusion on the extrinsic movements of the reticulorumen in conscious goats.…”
Section: Introductionmentioning
confidence: 93%
“…The changes in heart rate observed in our experiments with dopamine are difficult to interpret, since the cardiovascular effects can be caused by many factors changing cardiac function and peripheral resistance. In the dog, cardiovascular and renal effects of dopamine result from actions on a-and /?-adrenergic receptors and on specific dopamine receptors in the renal and mesenteric vascular beds (GOLDBERG, 1972). A small dose of dopamine stimulates cardiac contractility and output but also decreases total peripheral resistance by renal and mesenteric vasodilation.…”
Section: ; Titchen and Newhook 1968)mentioning
confidence: 99%